Pengolahan Limbah Organik Rumah Tangga Menjadi Cairan Multifungi di Dusun Pangeran Nato - Rahmadani, Shinta; Karinda, Karinda; Rahayu, Anggi Putri; Zuldekri, Putri; Rahmi, Rahmi (Jurnal Pengabdian Masyarakat Pinang Masak, 2023)
Prince Nato Hamlet is one of the hamlets located in Penyengat Olak Village, Jambi Outer City District, Muaro Jambi Regency, Jambi Province. Most of this area is planted with coconut trees (Cocos nucifera), areca nut (Areca catechu) and rice (Oryza sativa). The higher the agricultural activity in the hamlet, the impact on the organic waste produced. So far, the community has not managed this organic waste properly, so the Student Community Service Team took the initiative to provide counseling activities about the utilization of organic waste into a multifunctional liquid, namely eco-enzyme.